Development and assessment of the efficacy and safety of human lung-targeting liposomal methylprednisolone crosslinked with nanobody - Dong Weng; Zhao-Fang Yin; Shan-Shan Chen; Xian He; Nan Li; Tao Chen; Hui Qiu; Meng-Meng Zhao; Qin Wu; Nian-Yu Zhou; Li-Qin Lu; Dan-Li Tang; et al. (Drug Delivery, 2021)
Glucocorticoid (GC) hormone has been commonly used to treat systemic inflammation and immune disorders. However, the side effects associated with long-term use of high-dose GC hormone limit its clinical application seriously. GC hormone that can specifically target the lung might decrease the effective dosage and thus reduce GC-associated side effects. In this study, we successfully prepared human lung-targeting liposomal methylprednisolone crosslinked with nanobody (MPS-NSSLs-SPANb). Our findings indicate that MPS-NSSLs-SPANb may reduce the effective therapeutic dosage of MPS, achieve better efficacy, and reduce GC-associated side effects. In addition, MPS-NSSLs-SPANb showed higher efficacy and lower toxicity than conventional MPS.